Tinjauan Yuridis terhadap Eksekusi Jaminan Fidusia Hak Merek dalam Status Lisensi Aktif - Ayu Azalia Wardhani; Gunardi Lie (Jurnal Sostekmas: Jurnal Sosial, Teknologi, dan Pengabdian Masyarakat, 2025)
In Indonesia, economic development driven by the creative sector has given rise to the need to integrate Intellectual Property Rights (IPR) into the financing system, where trademarks, as one type of IPR, can be used as an object of fiduciary guarantee. However, the existence of an active license contract on a pledged trademark creates a conflict between the property rights of the creditor and the contractual rights of the licensee, which is not expressly regulated in the legislation. This study uses a normative juridical method with a statutory approach and qualitative analysis of relevant legal provisions. The results of the study indicate that although legally trademark rights can be used as an object of fiduciary guarantee, the execution process becomes complicated when the trademark is bound by an active license contract. The ambiguity in regulating the license status during execution slows down dispute resolution and increases risks for the parties involved. Therefore, clearer regulations regarding licensing arrangements in the context of fiduciary guarantees are urgently needed to improve the effectiveness and fairness of the execution.